Sejarah Perkembangan Yayasan Perguruan Al-Islam Di Surakarta Era Reformasi 1998-2015 - Asari, Retno Wulan Fitrimei; , Dr. Badaruddin, M.Ag; , Dr.ArI Anshori, M.Ag (2016)
Al-Islam collage foundation was established in Surakarta on 27th of Ramadan 1346 Hijriyah or 21st of March1928, on the stup KH. Imam Ghozali assisted by KH. Abdussomad and KH. Abdu Manaf. Al-Islam collagefoundation was originally a social institution of religious which themed central purification teachings of Islam, the unity of Muslims, and the realization of akhlak karimah with through the main line it is Islamic education. At the beginning of established, Al-Islam is not an organization but a movement that aims to bridge the opposition of Muslims in Indonesia, especially in Surakarta, there are modernists who want to reform Islamic thought and practice in communities, and the traditionalist group who wants to defending religious patterns are accommodating to the local culture. Therefor, would be interesting to know how the historical development of Al-Islam college foundation, after 87 years of existence, and the factors that influence its devellopment. During this reform era, Al-Islam college foundation has 11 institutions on TK/RA level, 7 institutions on SD/MI, 1 institution on junior high school level and 3 institutions on senior high school level that spread across Surakarta. However, in this reform era Al-Islam collage foundation stood, it still seems to be stagnant in thought and education, it can be seen from the quantity of students from each institution on various levels. In addition, the foundation is still glued to develop the institutions that already exist. There has been no new breakthrouhs to develop instutions to the college level, although some institutions are growing quiete rapidly such as TK/RA 1 Al-Islam and SD 2 Al-Islam. This research included in the quantitative research by describing the collecte data as the scope of his research. The obtained data presented descriptively using historical approach. Data collected by usng documentation, observation and interviews. Then the collected data, analyzed by qualitative analysis model and the conclusion presented deductively. Based on the analysis, researchers concluded that Al-Islam has a primary purpose as a modiator between the traditionalist group and the modernist groups. Modernist in its development appears not to be growing as fast as the two parties. Al-Islam collage foundation stagnate during the reform era, it was because the limiting factors are more dominant than the supporting factors. Some of them because the limited land less strategic school location, hampered by cost constraints and the many competitors that offer some of the advantages of the more interesting. Whereas, supporting factor is people still entrust Al-Islam college as an Islamic educational institution which have a good quality, it can be seen in terms of the religious experience is more advanced in the other Islam institutions.